2016
DOI: 10.1155/2016/4969523
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Dependent Differential Effect of Neurotrophic Factors on In Vitro and In Vivo Regeneration of Motor and Sensory Neurons

Abstract: Although peripheral axons can regenerate after nerve transection and repair, functional recovery is usually poor due to inaccurate reinnervation. Neurotrophic factors promote directional guidance to regenerating axons and their selective application may help to improve functional recovery. Hence, we have characterized in organotypic cultures of spinal cord and dorsal root ganglia the effect of GDNF, FGF-2, NGF, NT-3, and BDNF at different concentrations on motor and sensory neurite outgrowth. In vitro results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
50
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 50 publications
5
50
0
1
Order By: Relevance
“…By manipulating the composition of the inside matrix of each branch, we attempted to preferentially attract the regenerating motor and sensory axons and then selectively guide them towards different distal nerves and their corresponding targets. In accordance with similar studies with gap defects (Clements et al, ; Meyer et al, ; Santos, González‐Pérez, Navarro, & del Valle, ), the division of the tube in two separated compartments did not suppose an obstacle for nerve regeneration as all the operated animals showed regeneration distal to the tube and evidence of functional reinnervation of skin and muscles. Tube repair leaving a short gap between proximal and distal nerve stumps was first presumed to allow axons to be guided towards their original distal fascicle by means of neurotropic diffusible factors (Evans, Bain, Mackinnon, Makino, & Hunter, ; Rende, Granato, Lo Monaco, Zelano, & Tcesca, ).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…By manipulating the composition of the inside matrix of each branch, we attempted to preferentially attract the regenerating motor and sensory axons and then selectively guide them towards different distal nerves and their corresponding targets. In accordance with similar studies with gap defects (Clements et al, ; Meyer et al, ; Santos, González‐Pérez, Navarro, & del Valle, ), the division of the tube in two separated compartments did not suppose an obstacle for nerve regeneration as all the operated animals showed regeneration distal to the tube and evidence of functional reinnervation of skin and muscles. Tube repair leaving a short gap between proximal and distal nerve stumps was first presumed to allow axons to be guided towards their original distal fascicle by means of neurotropic diffusible factors (Evans, Bain, Mackinnon, Makino, & Hunter, ; Rende, Granato, Lo Monaco, Zelano, & Tcesca, ).…”
Section: Discussionsupporting
confidence: 88%
“…This result was corroborated by lack of differences in sensory functional recovery between both control and experimental groups. The lack of effect of LM + MP.NGF/NT‐3 on SNs was not expected as previous studies described a trophic and tropic guidance effect for laminin and NGF and NT‐3 individually assessed (Gallo et al, ; Santos, Giudetti, Micera, Navarro, & del Valle, , Santos, González‐Pérez, Navarro, & del Valle, ; Turney & Bridgman, ; Webber et al, ). One possible reason could be related with the heterogeneous populations of SNs (Usoskin et al, ) that reside in the DRG, in which approximately 70% of neurons express Trk receptors but of different subtypes whereas 30% are nonpeptidergic neurons and respond to Glial cell‐derived neurotrophic factor (GDNF) (Tucker & Mearow, ).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Curiously, the combination of fibres with GDNF led to poor neurite growth, as demonstrated by the low number and shorter neurites and a small occupied area detected in comparison to the control group. It is well known that GDNF sustains motor neuron survival and growth (Boyd and Gordon, ), however, it has been recently demonstrated that both low and high doses of GDNF are able to induce neurite outgrowth in cultured rat DRG (Santos et al, ). In cultured neurons, the expression of cRET is not changed in cells seeded on fibres, thus we can exclude that the absence of a GDNF‐based effect on fibres is due to a reduced number of GDNF‐responsive neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we used NVR gel as a carrier for neurotrophic factors. In particular, we focus our attention on glial cell line-derived neurotrophic factor (GDNF), which is mainly involved in motor neuron regrowth and remyelination [14][15][16]. After nerve injury, endogenous growth factors are released by neuronal and glial cells from the distal nerve stump, and they can stimulate and guide axon regeneration; yet, this support is ineffective in regeneration over long distance and extended in time due to the short life of neurotrophic factors and the decline of their production [17,18].…”
Section: Introductionmentioning
confidence: 99%